Figural Realism : Studies in the Mimesis Effect - White, Hayden V., 1928-2018 (Book collections on Project MUSE., 2019)
"In Figural Realism, White collects eight interrelated essays primarily concerned with the treatment of history in recent literary critical discourse. "'History' is not only an object we can study," White observes, "it is also and even primarily a certain kind of relationship to 'the past' mediated by a distinctive kind of written discourse. It is because historical discourse is actualized in its culturally significant form as a specific kind of writing that we may consider the relevance of literary theory to both the theory and the practice of historiography.""--Jacket